2015
DOI: 10.1007/s11104-015-2687-y
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in physiological responses between cyanobacterial and lichen crusts to a gradient of simulated nitrogen deposition

Abstract: Background and aims Nitrogen (N) deposition in arid lands is known to be increasing. However, N deposition gradients have unclear effects on physiological characteristics of biocrusts. This study tested if physiological characteristics are stimulated by low levels of N deposition and reduced by high levels of N deposition. Methods We simulated N deposition at various rates to plots of cyanobacterial and lichen biocrusts in the Gurbantunggut Desert and measured indicators of growth and stress. Results In cyanob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 76 publications
1
20
1
1
Order By: Relevance
“…Until now, only one study has recorded terrestrial algae in soils with an EC Sat up to 260 mS cm −1 (Tsujimura et al, 1998). Other studies on biocrusts on saline soils reported only sites with EC Sat values <30 mS cm −1 (e.g., Fox et al, 2009;Kidron, 2016;Sandoval Pérez et al, 2016;Schulz et al, 2016;Zhou et al, 2016;Ghiloufi et al, 2017;Kakeh et al, 2018). In the present study, however, much higher ranges of EC Sat (up to 950 mS cm −1 ) were documented, emphasizing the extreme soil salinities of the sampling sites.…”
Section: Soil Characteristics Reflect Extremely Saline Environmentscontrasting
confidence: 67%
“…Until now, only one study has recorded terrestrial algae in soils with an EC Sat up to 260 mS cm −1 (Tsujimura et al, 1998). Other studies on biocrusts on saline soils reported only sites with EC Sat values <30 mS cm −1 (e.g., Fox et al, 2009;Kidron, 2016;Sandoval Pérez et al, 2016;Schulz et al, 2016;Zhou et al, 2016;Ghiloufi et al, 2017;Kakeh et al, 2018). In the present study, however, much higher ranges of EC Sat (up to 950 mS cm −1 ) were documented, emphasizing the extreme soil salinities of the sampling sites.…”
Section: Soil Characteristics Reflect Extremely Saline Environmentscontrasting
confidence: 67%
“…In addition, the redundant oxygen and peroxides can be eliminated by synthesizing superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and other antioxidant enzymes34353637. These osmotic adjustment substances and antioxidants can also be synthesized by plants when they are subjected to salt stress, heavy metal pollution, UV-B radiation and other stress environments38394041. Studies have also shown that the responses to UV-B radiation involve the increase of the relative proportions of photo-protective compounds in plants, such as β-carotene, zeaxanthin, and violaxanthin1842.…”
mentioning
confidence: 99%
“…The dominant plants are Haloxylon ammodendron and H. persicum [43]. In addition to this, there are many biological soil crusts, containing cyanobacteria-dominated, lichen-dominated, and moss-dominated crusts [44]. The soil in the desert has a sandy texture, with sand (0.05-2 mm) content, 85%; silt (0.002-0.05 mm) content, 13.7%; and clay (< 0.002 mm) content, 1.3%.…”
Section: Measurement Sitementioning
confidence: 99%